Respostas

2012-12-16T11:41:13-02:00

veja se isto te ajuda :

 

 

f ( -1) = -4x - 6                                f (-2) = -4x - 6                                  f ( -6) = -4x -6 

f ( -1) = ( -4 ) . ( -1 ) - 6                  f (-2) = (-4) . (-2) - 6                        f (-6) = (-4) . (-6) - 6

f (-1 ) =  4 - 6                                  f (-2) = 8 - 6                                     f (-6) = 24 -6

f (-1 ) = - 2                                      f (-2) = 2                                           f (-6) = 18

 

f(-1) + f(-2) - f(-6) =   -2 + 2 - 18 = -18

2012-12-16T12:35:03-02:00

Quando e dado F(-1) por exemplo e so vc substituir o numero dentro do parentese pelo x

f(-1)=-4(-1)-6

f(-1)= 4-6

f(-1)=-2

 

f(-2)=-4(-2)-6

f(-2)=8-6

f(-2)=2

 

f(-6)=-4(-6)-6

f(-6)=24-6

f(-6)=18

 

(-2)+(-6)-(18)=-26